The Influence of Work Discipline and Work Environment on Motivation That Has an Impact on Employee Performance at PT. Pan Brothers Tbk In Tangerang - Asmalah, Lia (PINISI Discretion Review, 2022)
This study aims to determine the effect of work discipline and work environment on motivation which has an impact on employee performance at PT. Pan Brothers Tbk in Tangerang. The method used is explanatory research with a sample of 100 respondents. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study that work discipline has a significant effect on motivation by 39.3%, hypothesis testing obtained a significance of 0.000 <0.05. The work environment has a significant effect on motivation by 39.0%, hypothesis testing obtained a significance of 0.000 <0.05. Work discipline and work environment simultaneously have a significant effect on motivation by 50.0%, hypothesis testing is obtained a significance of 0.000 <0.05. Motivation has a significant effect on employee performance by 38.4%, hypothesis testing is obtained a significance of 0.000 <0.05.